An Analysis of the Perceptions of Regulatory Authorities about the Causes of Non-Performing Loans - Bhattarai, Seema (Journal of Business and Social Sciences Research, 2020)
The purpose of this study is to identify the causes of non-performing loans (NPAs) from regulators’ perspective and ways to minimise it. The primary data through two interviews from two regulators are taken as a method of data collection. The major findings of the study are that pressure to remain profitable by banks, personal problems; lack of best banking practice, professionalism, earthquake, conflict period, economic cycle may be the reasons behind high non-performing loan in Nepal. Regulators perceived that prudent credit assessment and decision; counselling of customer problem and development of prudent credit culture may help to reduce non-performing loans in Nepal.